TWIN SISTER OF FT (TSF) Interacts with FRUCTOKINASE6 and Inhibits Its Kinase Activity in Arabidopsis - Jin, Suhyun; Kim, Sun Young; Ahn, Ji Hoon (Frontiers in Plant Science, 2017)
In flowering plants, the developmental switch to the reproductive phase is tightly regulated and involves the integration of internal and external signals. FLOWERING LOCUS T (FT) and TWIN SISTER OF FT (TSF) integrate signals from multiple pathways. FT and TSF function as florigenic substances, and share high sequence similarity with mammalian Raf kinase inhibitor protein (RKIP). Despite their strong similarity to RKIP, the kinase inhibitory activity of FT and TSF remains to be investigated. We performed a yeast two-hybrid screen and found that TSF interacted with FRUCTOKINASE6 (FRK6), which phosphorylates fructose for various metabolic pathways. Among the seven Arabidopsis FRKs, FRK6 and FRK7 have high sequence similarity; therefore, we investigated whether TSF interacts with FRK6 and FRK7. In vitro pull-down assays and bimolecular fluorescence complementation assays revealed that TSF interacts with FRK6 in the nucleus, but not with FRK7. Kinase activity assays suggested that TSF inhibits the kinase activity of FRK6, whereas FT does not. By contrast, neither TSF nor FT inhibits the kinase activity of FRK7. The frk6 and frk7 mutants show slightly delayed flowering, but only under short-day conditions. Plastochron length is also affected in both frk6 and frk7 mutants under short-day conditions. FT expression levels decreased in frk6 mutants, but not in frk7 mutants. Taken together, our findings suggest that TSF physically interacts with FRK6 and affects its kinase activity, whereas FT does not, although these proteins share high sequence similarity.